Problem of justice in Plato’s philosophy - Сабадуха, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article studies the problem of justice in Plato’s philosophy in the context of the existential problems of human existence and the process of creating a state.